Pengaruh Akupresure Terhadap Kuantitas Tidur Balita - Cahyati Fitri Mumpuni; Enny Yuliaswati (Jurnal Anestesi, 2023)
Background : Sleep disturbances in children are often complained of by parents, where sleep disturbances in children under five are 44.2%. A toddler's sleep quantity will greatly affect his growth, if a child has poor sleep quantity (<11 hours/day) then this will also have a negative impact on the child's growth. Interventions that can be done to meet toddlers' sleep needs are by means of acupressure therapy. Acupressure is stimulation of acupuncture points with pressure that stimulates sensory nerve cells in the acupuncture point area thereby increasing local endorphins production and relieving pain in certain areas. Purpose: To analyze the effect of acupressure on the quantity of sleep for toddlers in the RW 12 Rejosari Karanggeneng Boyolali area. Method : This type of research is pre-experimental with one grub design (before and after) treatment. The sample obtained is from the calculation of the freeder formula plus 30% of the total sample calculation results, namely as many as 21 toddlers. Results: The results of the study with the Wilcoxon Signed Rank test obtained a P value = 0.000 where the P value is smaller ? (0.005) meaning that there is an effect of giving acupressure on the quantity of sleep for toddlers. Conclusion: There is an effect of acupressure on the quantity of sleep for toddlers in the RW 12 Rejosari Karanggeneng Boyolali area.